Towards ultrahigh-resolution multi-reflection time-of-flight mass spectrometry at ISOLTRAP. (26th November 2015) - Wienholtz, F; Atanasov, D; Kreim, S; Manea, V; Rosenbusch, M; Schweikhard, L; Welker, A; Wolf, R N
Abstract: The mass resolving power of the multi-reflection time-of-flight mass spectrometer of ISOLTRAP was studied by monitoring 39 K + signals. A drift tube at the center of the MR-ToF MS allows decreasing or increasing the kinetic energy of the ion bunch, by switching its potential when the ions are traversing it. This offers the possibility of capturing and ejecting ion bunches by controlling a single voltage by the so-called in-trap lift technique. It also allows changing the energy of the trapped ions inside the MR-ToF MS, offering a way to optimize the resolving power of the device. For a fixed number of 2000 laps corresponding to a total ion flight time of about 30 ms, data was accumulated for 100 experimental cycles, adding to a duration of 10 s for each spectrum. Without any subsequent corrections for broadening effects, mass resolving powers in excess of 300 000 (FWHM) were obtained.